Organochlorine pesticides in Muraena helena L. 1758 from the Eastern Adriatic Sea. (26th December 2013) - Đikić, D.; Mojsović Ćuić, A.; Jurak, G.; Lasić, D.; Skaramuca, D.; Matić‐Skoko, S.; Tutman, P.; Bošnir, J.; Franjević, D.; Franić, Z.; Fuchs, R.; Skaramuca, B.
Summary This work examines the bioaccumulated organochlorine compounds in Muraena helena to draw attention to this species as a potential bioindicator organism. The morays were caught in the East Adriatic Sea, Elaphite Islands, near Dubrovnik, Croatia (lat: 42°45′38.8″; long: 17°45′53.6″) at the same location in summer (August, 2009) and winter (January, 2010), at depths from 5 to 10 m. Nine fish were caught by longline hooks per each field trip (total in summer and winter, N = 18). No single fish was free of organochlorines (OC), but not all pesticides were present in every fish. The concentration level was: Endrin > ppDDE > Heptachlor epoxide > Heptachlor > Aldrine > Lindane > βHCH > δHCH > Endrin aldehyde). Endrin was the only pesticide approaching the maximum concentrations proposed by the European Union and Croatia (summer max. concentration = 14.75 μg kg−1; winter max. concentration = 8.35 μg kg−1). All other pesticides ranged from 0.1 to 0.7 μg kg−1. Heptachlor was absent in winter and δ‐HCH and Endrin aldehyde in summer, while Lindane and pp‐DDE had higher (P ≤ 0.05) concentrations in summer. Other residues had similar seasonal concentration levels. The p‐DDT was similar as in other biota from the Adriatic or Mediterranean. HCH concentrations corresponded to those found in organisms from the Italian area of the Adriatic. The endocrine and reproductive disrupting potential of the detected OCs are bases for future studies. Results show that morays are a good bioindicator model, with slight interspecies and seasonal variability in OC bioaccumulation as a consequence of diverse food consumption.